2011
DOI: 10.1177/016235321103400303
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics for Gifted Students in an Arts- and Technology-Rich Setting

Abstract: In this paper we report on a study of a short-term mathematics program for grade 7-8 gifted students that integrated open-ended mathematics tasks with the arts (poetry and drama) and with technology. The program was offered partially online and partially in a classroom setting. The study sought to investigate (a) students' perceptions of their school-based mathematics experience, (b) students' perceptions of the program we offered, and (c) students' mathematical thinking while engaged in the activities of our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 23 publications
2
18
0
3
Order By: Relevance
“…This finding lends additional support to a body of research that shows that writing in mathematics can induce students to think logically and explain their thought process (Bicer et al, 2013;Devlin, 2012;NCTM, 2014;Pugalee, 2004). Moreover, providing digital writing environments can enhance the learning process for students who may have learning disabilities (Huscroft-D'Angelo et al, 2015), as well as for students who are gifted (Gadanidis et al, 2011). Many students, particularly in Study A (the younger students), also relayed their mathematical understanding through the drawing of pictures.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This finding lends additional support to a body of research that shows that writing in mathematics can induce students to think logically and explain their thought process (Bicer et al, 2013;Devlin, 2012;NCTM, 2014;Pugalee, 2004). Moreover, providing digital writing environments can enhance the learning process for students who may have learning disabilities (Huscroft-D'Angelo et al, 2015), as well as for students who are gifted (Gadanidis et al, 2011). Many students, particularly in Study A (the younger students), also relayed their mathematical understanding through the drawing of pictures.…”
Section: Discussionsupporting
confidence: 67%
“…Research has shown strong connections between students' writing abilities and their capacity to learn in general (US National Institute for Literacy, 2007), to learn new mathematics content Meel, 1999), to improve mathematics problem-solving skills (Bicer et al, 2013;Pugalee, 2004), and to augment processes related to cognition (Flower, Schriver, Carey, Haas, & Hayes, 1992). Gadanidis, Hughes, and Cordy (2011) found that students in middle school, who are gifted, successfully used multiple modes of communication, including drawing, writing, and an online discussion forum to learn mathematics.…”
Section: Learning and Communicating Mathematical Ideas Through Writingmentioning
confidence: 99%
“…La mayor parte de las publicaciones se centran en la escuela, concretamente en asignaturas STEM, por ejemplo, los trabajos de Mun y Hertzog (2018), Tofel-Grehl, Feldon y Callahan (2018) y Olszewski-Kubilius (2010). Otro de los trabajos analizados enlaza estas materias con la poesía y el drama (Gadanidis, Hughes, & Cordy (2011), y tan sólo un estudio se centra en la escritura (Nettleton, 2014). Además, hay algún trabajo que va más allá de lo académico, que incluye la educación para la ciudadanía (Gibson, Rimmington, & Landwehr-Brown, 2008), o la atención al alumnado con AACC desde la extraescolaridad (Lutsik, Sobolev, & Isaev, 2018).…”
Section: Análisis De Contenidounclassified
“…However, various studies about characteristics of elementary mathematics students illustrate that it is hard to define stereotyping image of elementary mathematics students (e.g. Maloney, Risko, Ansari & Fugelsang, 2010;Gadanidis, Hughes & Cordy, 2011;Thornton, 1997). Although a teacher may use proper mathematics representations, it would be meaningless if students cannot understand them.…”
Section: Interpretations and Questionsmentioning
confidence: 99%